Proposed clinical pathway for nonoperative management of high-grade pediatric pancreatic injuries based on a multicenter analysis: A pediatric trauma society collaborative. Issue 4 (October 2017) - Naik-Mathuria, Bindi J.; Rosenfeld, Eric H.; Gosain, Ankush; Burd, Randall; Falcone, Richard A.; Thakkar, Rajan; Gaines, Barbara; Mooney, David; Escobar, Mauricio; Jafri, Mubeen; Stallion, Anthony; Klinkner, Denise B.; et al.
Abstract : BACKGROUND: Guidelines for nonoperative management (NOM) of high-grade pancreatic injuries in children have not been established, and wide practice variability exists. The purpose of this study was to evaluate common clinical strategies across multiple pediatric trauma centers to develop a consensus-based standard clinical pathway. METHODS: A multicenter, retrospective review was conducted of children with high-grade (American Association of Surgeons for Trauma grade III-V) pancreatic injuries treated with NOM between 2010 and 2015. Data were collected on demographics, clinical management, and outcomes. RESULTS: Eighty-six patients were treated at 20 pediatric trauma centers. Median age was 9 years (range, 1–18 years). The majority (73%) of injuries were American Association of Surgeons for Trauma grade III, 24% were grade IV, and 3% were grade V. Median time from injury to presentation was 12 hours and median ISS was 16 (range, 4–66). All patients had computed tomography scan and serum pancreatic enzyme levels at presentation, but serial enzyme level monitoring was variable. Pancreatic enzyme levels did not correlate with injury grade or pseudocyst development. Parenteral nutrition was used in 68% and jejunal feeds in 31%. 3Endoscopic retrograde cholangiopancreatogram was obtained in 25%. An organized peripancreatic fluid collection present for at least 7 days after injury was identified in 59% (42 of 71). Initial management of these included: observation 64%, percutaneous drain 24%, and endoscopic drainage 10% and needle aspiration 2%. Clear liquids were started at a median of 6 days (IQR, 3–13 days) and regular diet at a median of 8 days (IQR 4–20 days). Median hospitalization length was 13 days (IQR, 7–24 days). Injury grade did not account for prolonged time to initiating oral diet or hospital length; indicating that the variability in these outcomes was largely due to different surgeon preferences. CONCLUSION: High-grade pancreatic injuries in children are rare and significant variability exists in NOM strategies, which may affect outcomes and effective resource utilization. A standard clinical pathway is proposed. LEVEL OF EVIDENCE: Therapeutic/care management, level V (case series).